A BASELINE STUDY ON MACROZOOBENTHOS ASSEMBLAGES IN PASIR ISLAND - Prasetiya, Fiddy Semba; Nurrahman, Yusuf Arief; Zalessa, Sheila; Astuty, Sri; Riyantini, Indah; Faizal, Ibnu (JFMR (Journal of Fisheries and Marine Research), 2020)
Biodiversity of macrozoobenthos in Pasir Island, Brebes, is under-explored. On the other hand, the baseline information regarding macrozoobenthos is essentially required for better future environmental management. This research aims to analyze macrozoobenthos community structure in the Pasir Island that has not been documented. Surveys were carried out in the rainy season. In this study, a total of 10 sampling locations were classified into two different groups that represent â€œcontrolâ€ and â€œdisturbedâ€ station. The main structural parameters of the macrozoobenthos identified at each station were specific richness (S), abundance (number of individuals m-2, N) and the Pielouâ€™s index (J). Additionally, the pairwise comparison between groups was conducted by using analysis of similarity (ANOSIM) and the similarity percentage (SIMPER) to obtain the description of community structure. A total of 1054 specimens were counted from the â€œcontrolâ€ and â€œdisturbedâ€ stations. These specimens belonged to five animal classes, namely, Bivalvia, Gastropoda, Malacostraca, Cephalopoda and Echinoidea. ANOSIM and SIMPER analysis demonstrated that a significant difference was found between â€œcontrolâ€œ andÂ  â€œdisturbedâ€œ stations with the percentage of dissimilarity value of 88.82%. In addition, environmental variables such pH, salinity and type of substrates contributed significantly to this difference. This result provides insight regarding macrozoobenthos diversity and ecological information that may contribute to further conservation management in the Pasir Island, Indonesia.